Women Empowerment in Punjab: Dimensions, Determinants, and Implications for Access to Healthcare - Ahmad, Dilshad; Shah, Salyha Zulfiqar Ali; Bashir, Furrukh (Pakistan Journal of Humanities and Social Sciences, 2021)
In developing countries like Pakistan, because of the complex cultural and socio-demographic milieu women empowerment always remained the contested issue. Overall major indicators of human development of women have been considered lower rather than men. In Pakistan, some considerable measures have focused on women's empowerment however, their status is still miserable specifically in rural areas. This study was aimed to find out, the extent of rural women empowerment and the effect of women empowerment regarding access to healthcare in the Vehari district of Southern Punjab, Pakistan. The study used data of 240 married women respondents and employed Cronbach’s alpha and OLS approaches for various analyses of the study components. Scores of various components regarding women's empowerment were regressed over the scores of women's access to healthcare in the final analysis of the study. The finding of the study indicated that the power of decision-making (0.87), self-esteem (0.79), and mobility (0.89) has positive and significant effects on access to health care whereas control over the resource (0.73) estimates indicated positive while the insignificant impact on health access. Education access, adequate job opportunities, and media information approach considered more appropriate and feasible measures for adequate women empowerment and health care access. Emergency-based State-based policy measures need to be applied such as women schooling at doorstep, increasing females' priority-based job opportunities, and proper access to media for increasing awareness regarding their rights and significant role in society.